So chef, does a PhD matter? A Malaysian perspective(s) on Bucher and Lee - Zainal Abidin, Muhammad Rezza; Basar, Zulfikry (Elsevier, 2024)
This paper offers a critical reflection on the challenges culinary professionals encounter when venturing into academia. We directly respond to Bucher and Lee's (2023) article, "Dear chef, do you really want a PhD?". Bucher and Lee aptly illuminated the intricacies, challenges, hurdles, and barriers that chefs face when pursuing a doctoral education in the hospitality academy. We add to Bucher and Lee's work, providing not only a more nuanced perspective, but also a counternarrative from two different voices acknowledging; (i) the voluntary pursuit of a PhD driven by personal choice and, (ii) the compelled pursuit imposed by organisational pressures. This reflective analysis aims to deepen the understanding of the multifaceted dynamics involved in the intersection of culinary expertise and academic pursuits.